Biodegradation of sulfamethoxazole in bacteria from three different origins. (15th January 2018) - Mulla, Sikandar I.; Hu, Anyi; Sun, Qian; Li, Jiagwei; Suanon, Fidèle; Ashfaq, Muhammad; Yu, Chang-Ping
Abstract: Sulfamethoxazole (SMX) is a common medicine prescribed to treat infections. Due to vast use, SMX has been detected in different parts of the world. Hence, it has become a high risk because of its long term persistence with high biological activity in the ecosystem. Therefore, it is necessary to understand the mechanism of SMX degradation in different genus of bacteria, which is presently unclear. In the present study, degradation of 5 mg L −1 SMX was studied in three isolated pure bacterial cultures, Ochrobactrum sp. SMX-PM1-SA1, Labrys sp. SMX-W1-SC11 and Gordonia sp. SMX-W2-SCD14 and results showed up to 45.2%, 62.2% and 51.4% degradation, respectively within 288 h. Additionally, strain SA1 and strain SCD14 showed up to 66.2% and 69.2% of 4-aminophenol degradation at an initial concentration of 5 mg L −1 within 216 h whereas Labrys sp. SMX-W1-SC11 completely degraded 4-aminophenol at the same concentration within 120 h. Moreover, all three pure bacteria also completely degraded 3-amino-5-methylisoxazole at initial concentration of 4 mg L −1 within 120 h. Furthermore, gas chromatography-mass spectrometry and quadrupole time-of-flight mass spectrometry analysis results revealed that 3-amino-5-methylisoxazole, 4-aminophenol and hydroquinone were the three main by-products of SMX catabolism. In addition, cell free extracts of both Labrys sp. SMX-W1-SC11 and Gordonia sp. SMX-W2-SCD14 showed hydroquinone dioxygenase activity. Besides, all three bacterial strains showed resistance to different heavy metals. Moreover, all three pure bacterial cultures also showed positive chemotactic response toward 3-amino-5-methylisoxazole and hydroquinone based on the drop plate assay. The results of this study recommend these microorganisms for bioremediation of SMX contaminated sites. Highlights: Ochrobactrum sp. SA1 showed up to 45.2% degradation of SMX at 5 mg L −1 . Labrys sp. SC11 showed up to 62.2% degradation of SMX at 5 mg L −1 . Gordonia sp. SCD14 showed up to 51.4% degradation of SMX at 5 mg L −1 . 3-amino-5-methylisoxazole, 4-aminophenol and hydroquinone are the intermediates. Cell free extracts of SC11 and SCD14 showed hydroquinone dioxygenase activity.